The secret life (cycle) of temperate bacteriophages - Fillol-Salom,A; Bacigalupe,R; Humphrey,S; Chiang,YN; Chen,J; Penadés,JR (2021)
Abstract Lysogenic induction ends the stable association between a bacteriophage and its host, and the transition to the lytic cycle begins with prophage e xcision followed by DNA r eplication and p ackaging (ERP) – a temporal program that is considered universal for most temperate phages. Here we report that the long-standing ERP program is an artefact of the experimentally favoured Salmonella phage P22 ts c 2 29 heat-inducible mutant, and that wildtype P22 actually follows a replication-packaging-excision (RPE) program. We found that unlike P22 ts c 2 29 , P22 delayed excision to just before it was detrimental to phage production. Thus, at minimal expense to itself, P22 has tuned the timing of excision to balance propagation with lateral transduction, powering the evolution of its host through gene transfer in the interest of self-preservation. One Sentence Summary Genetic analyses propose a new life cycle for temperate bacteriophages.